Pengaruh Bauran Pemasaran Syariah (9P) Terhadap Keputusan Pembelian Perumahan di Kota Pekanbaru - Sholahuddin, Sholahuddin (Sekolah Tinggi Ilmu Ekonomi Mahaputra Riau, 2021)
As the population increases both due to birth rates and due to immigrants to an area, then automatically the human need for shelter in the area will increase. This phenomenon is a promising business opportunity for housing developers. The housing business opportunity lures entrepreneurs to expand their business wings by offering various types and models of housing to prospective customers. This condition has a positive impact on people who need a house as a place to live. In this regard, this study will analyze the effect of the Islamic marketing mix (9P) on housing purchase decisions in the city of Pekanbaru. With quantitative methods, this research is a field research where the data collection technique is by distributing questionnaires to 100 respondents and conducting interviews with housing developers and marketing who are the object of research in the city of Pekanbaru. The results of this study indicate that there is a significant positive influence on product, price, place, promotion, people, process, physical evidence, promise, and petience on the housing purchase decision in Pekanbaru both persially and simultaneously.